2001
DOI: 10.1016/s1525-1578(10)60670-8
|View full text |Cite
|
Sign up to set email alerts
|

Robot Printing of Reverse Dot Blot Arrays for Human Mutation Detection

Abstract: We report on a generally useful, partially automated, human mutation detection method based upon printing moderate density oligonucleotide arrays using a biorobot on activated nylon membranes. The Beckman Biomek 2000 was adapted to this task through fabrication of aluminum membrane filter holders and the development of an addressable Tool Command Language (Tcl) program, which can be invoked through BioScript. During program execution, a robot arm is moved along the x, y, and z axes to expel liquid, without dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…This method is a simple, rapid and reliable method which allows simultaneous detection of up to 20 different mutations or polymorphisms in a single hybridization assay [32]. There are three common alleles at this locus with 5, 7 and 9 thymidines (T 5 , T 7 , T 9 ) that could influence the processing of exon 9 in the mRNA of CFTR gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method is a simple, rapid and reliable method which allows simultaneous detection of up to 20 different mutations or polymorphisms in a single hybridization assay [32]. There are three common alleles at this locus with 5, 7 and 9 thymidines (T 5 , T 7 , T 9 ) that could influence the processing of exon 9 in the mRNA of CFTR gene.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse Dot Blot reaction was performed according to Lappin et al [32]. In this assay, oligonucleotide probes were synthesized using a C6-amino-linker on the 5' end of the product and were attached onto Biodyne C nylon membrane (from Pall Corporation) activated by 1-Ethyl 3-Dimethyl Aminopropyl Carbodiimide (EDAC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse dot-blot is a widely used tool for routine screening of numerous mutant alleles in the HBA2/HBA1 [Chan et al, 1999, Foglietta et al, 2003] and HBB genes [Cai et al, 1994, Winichagoon et al, 1999. Automated platforms for preparing the reverse dot-blot membranes (strips) have been reported that allow printing of large numbers of strips with higher-density arraying [Lappin et al, 2001] and hence commercialization of the entire process.…”
Section: Methodology Overview: Symphony Of Athousandmentioning
confidence: 99%
“…PCR for DNA extracted from a paraffin section, and in situ PCR were performed using degenerative primers to detect cutaneous type HPV (3,4). PCR primers for ß-globin were used as positive control (5). No cutaneous type HPV was detected by either analysis (data not shown).…”
Section: Case Reportmentioning
confidence: 98%